THE INFLUENCE OF HUMAN RESOURCES, CAREER AND EMPLOYEE WELFARE ON COMPANY DEVELOPMENT - Stanty Aufia Rachmat; Arman Syah Putra; Nurul Aisyah; Endah Prawesti Ningrum; Bryan Givan; Muhammad Yunus Rangkuti (Journal of Innovation Research and Knowledge, 2022)
The background of this research is to raise the variables of human resources, career, and employee welfare to the development of the company, with the variables raised in this study, it can be seen which variables can significantly influence the variables of company development. The method used in this research is quantitative method by conducting a survey to 100 employees in a company to find out the development of the company which is influenced by the variables in this study. The problem raised in this research is how to process data taken from a company that contains 100 people, data taken from the employee so that it can answer research problems that know what variables affect the company development variables. The purpose of this study is how to determine the relationship between career human resources variables and employee welfare on company development. With significant results on all variables, the variables above affect other variables.